2018
DOI: 10.1186/s12906-018-2110-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-acute oral toxicity of Dracaena cinnabari resin methanol extract in rats

Abstract: BackgroundDracaena cinnabari (DC) is a perennial tree that located on the Southern coast of Yemen native to the Socotra Island. This tree produces a deep red resin known as the Dragon’s blood, the Twobrother’s Blood or Damm Alakhwain. The current study performed to evaluate the safety of the DC resin methanol extract after a single or 28 consecutive daily oral administrations.MethodsIn assessing the safety of DC resin methanol extract, acute and sub-acute oral toxicity tests performed following OECD guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 22 publications
3
29
0
1
Order By: Relevance
“…Furthermore, the histopathology examination showed no histopathological lesions in the liver, kidneys or heart after treatment with CSE. The assessment of histopathological alterations in organs is considered a basic test in the safety assessment of tested materials [48]. These results reinforce the findings of the absence of toxicity after treatment with 1 g/kg b.w.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, the histopathology examination showed no histopathological lesions in the liver, kidneys or heart after treatment with CSE. The assessment of histopathological alterations in organs is considered a basic test in the safety assessment of tested materials [48]. These results reinforce the findings of the absence of toxicity after treatment with 1 g/kg b.w.…”
Section: Discussionsupporting
confidence: 71%
“…for 28 days. On the other hand, damage or destruction of blood cells negatively affects the normal functioning of the body in both humans and animals [48]. The analysis of erythrocytes, leukocytes and platelets showed the absence of alterations in these parameters after treatment with CSE as well.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of therapeutic window is also an important parameter that provides benefit to risk assessment of the drug/compound, animal model is one of the approach to unveil this aspect (Al-Afifi et al, 2018). Normal food and water intake throw light on the normal metabolic processes, as observed in the treated animals (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Result of hematological analysis revealed that AA might have normal role in the production and development process of blood cells, as the data shows non-significant alterations in the treatment vs control group (Table 5). Hematological parameters point out minor and major alterations in the functioning of different organs (Al-Afifi et al, 2018). Moreover, our finding is supported by the previous researchers (Petterino & Argentino-Storino, 2006; Said & Abiola, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of therapeutic window is also an important parameter that provides benefit to risk assessment of the drug/compound, animal model is one of the approach to unveil this aspect (Al-Afifi et al 2018). Normal food and water intake throw light on the normal metabolic processes, as observed in the treated animals ( Table 4) Manuscript to be reviewed understanding of any signs of toxicity, as hematological system is very sensitive against the effects of any toxin entering living system and have higher diagnostic value for signs of intoxication (Olson et al 2000).…”
Section: Discussionmentioning
confidence: 99%